Entrepreneurship in transition economies: the role of institutions and generational change - Saul Estrin; Tomasz Mickiewicz (Institute for the Study of Labor (IZA), 2010)
The transition economies have lower rates of entrepreneurship than are observed in most developed and developing market economies. The difference is even more marked in the countries of the former Soviet Union than those of Central and Eastern Europe. We link these differences partly with the legacy of communist planning, which needs to be replaced with formal market-supporting institutions. But many of these developments have now taken place, yet entrepreneurial activity still remains low in many places. To analyse this longer term issue, we highlight the necessarily slow pace of development of new informal institutions and the corresponding social attitudes, notably rebuilding the generalised trust. We argue that changes are even slower in the former Soviet Union than Central and Eastern Europe because communist rule was much longer, leading to a lack of institutional memory. We posit that changes in informal institutions may be therefore delayed until after full generational change.
Keywords: L26; O17; O57; 330; Entrepreneurship; formal and informal sectors; shadow economy; institutional arrangements; comparative studies of countries; Unternehmer; Übergangswirtschaft; Wirtschaftssoziologie; Institutioneller Wandel; Generationenbeziehungen; Vergleich; Osteuropa; Russland